The Rise and Fall of the Welfare State - Wahl, Asbjørn (Pluto Press, 2011)
In an age of government imposed austerity, and after 30 years of neoliberal restructuring, the future of the welfare state looks increasingly uncertain. Asbjorn Wahl offers an accessible analysis of the situation across Europe, identifies the most important challenges and presents practical proposals for combating the assault on welfare. Wahl argues that the welfare state should be seen as the result of a class compromise forged in the 20th century, which means that it cannot easily be exported internationally. He considers the enormous shifts in power relations and the profound internal changes to the welfare state which have occurred during the neoliberal era, pointing to the paradigm shift that the welfare state is going through. This is illustrated by the shift from welfare to workfare and increased top down control. As well as being a fascinating study in its own right that will appeal to students of economics and politics, The Rise and Fall of the Welfare State also points to an alternative way forward for the trade union movement based on concrete examples of struggles and alliance-building.